Combinatory repair strategy to promote axon regeneration and functional recovery after chronic spinal cord injury - DePaul, Marc A. (Sci Rep, 2017)
Eight weeks post contusive spinal cord injury, we built a peripheral nerve graft bridge (PNG) through the cystic cavity and treated the graft/host interface with acidic fibroblast growth factor (aFGF) and chondroitinase ABC (ChABC). This combinatorial strategy remarkably enhanced integration between host astrocytes and graft Schwann cells, allowing for robust growth, especially of catecholaminergic axons, through the graft and back into the distal spinal cord. In the absence of aFGF+ChABC fewer catecholaminergic axons entered the graft, no axons exited, and Schwann cells and astrocytes failed to integrate. In sharp contrast with the acutely bridge-repaired cord, in the chronically repaired cord only low levels of serotonergic axons regenerated into the graft, with no evidence of re-entry back into the spinal cord. The failure of axons to regenerate was strongly correlated with a dramatic increase of SOCS3 expression. While regeneration was more limited overall than at acute stages, our combinatorial strategy in the chronically injured animals prevented a decline in locomotor behavior and bladder physiology outcomes associated with an invasive repair strategy. These results indicate that PNG+aFGF+ChABC treatment of the chronically contused spinal cord can provide a permissive substrate for the regeneration of certain neuronal populations that retain a growth potential over time, and lead to functional improvements.